Determination of glycemic index and glycemic load of some widely consumed foods in Syrian society - صارم زينب; قفوره عفراء (Latakia University Journal -Medical Sciences Series, 2022)
The glycemic index is a measure of the ability of carbohydrates in foods to raise blood glucose compared to reference glucose. It is designed to help people with or at risk of diabetes choosing healthy diets that maintain their health and prevent complications. Several studies have been conducted that determined the values ​​of the glycemic index for many foodstuffs, but the majority of these materials were composed of one food component, while our diet depends mostly on mixed meals consisting of more than one food component, and they differ in their components and methods of preparation from one country to another, where there is no information about the value of its glycemic index, this study aimed to study the value of each of the glycemic index and glycemic load of three meals commonly consumed by us in Syria, which are grape leaves stuffed with rice (yabrak), rice with pea broth, and bulgur with chickpeas and determine its suitability for people with diabetes or at risk of developing it. The study included 10 healthy people, their ages ranged between (20-30) years, who do not take any medications, and do not suffer from obesity, diabetes, glucose intolerance or high blood lipids. On the first day of the study, each of the participants in the study ate on an empty stomach (after an overnight fast) a specific amount of white bread (reference food) containing (50) g ​​of digestible and absorbable carbohydrates, their blood glucose was measured using a home glucose analyzer, after (0-30-60-90-120) minutes from eating the meal, this process was repeated on other separate days, but by eating a specific amount of one of the three previously mentioned dishes, which also contains (50) g ​​of digestible carbohydrates each time. The arithmetic mean of the blood glucose values ​​of the volunteers was calculated at each time interval and every meal thoughtful, then the graph was drawn for it, and the value of each glycemic index and glycemic load was calculated. The value of each glycemic index and glycemic load for stuffed grape leaves was 74.67, 23.72 for rice with pea broth was 92.23, 22.31 and for bulgur with chickpeas 35.23, and 14.67, respectively, this indicates the suitability of eating bulgur by people with diabetes for their health status and the unsuitability of both grape leaves stuffed with rice and rice with pea broth for them.